Acute hydrogen-rich water ingestion stimulates cardiac autonomic activity in healthy females - Botek, Michal; Sládečková, Barbora; Krejčí, Jakub; Pluháček, František; Najmanová, Eliška (Acta Gymnica, 2021)
Background: Hydrogen-rich water (HRW) has been shown to have a stimulating effect on the human body. Objective: The aim of the study was to assess the influence of acute HRW intake on autonomic cardiac regulation during 50 min of rest sitting. Methods: Fourteen healthy females (age 21.7 ± 1.2 years, body mass 67.8 ± 8.7 kg, height 167 ± 5.5 cm) took part in this double-blind, randomized, placebo-controlled trial with crossover design. Heart rate variability (HRV) was monitored in the sitting position after administration of 1260 ml of HRW or placebo. Time domain indexes of HRV as the square root of the mean of the squares of differences between adjacent RR intervals (RMSSD), the standard deviation of all RR intervals (SDNN) and the ratio of SDNN/RMSSD as an index of sympatho-vagal balance were used to assess autonomic cardiac response. The values were transformed using natural logarithm (Ln). Results: After administration of HRW, we found significantly increased ratio Ln SDNN/RMSSD when comparing it to placebo in 25 min (HRW: 0.40 ± 0.30, placebo: 0.26 ± 0.25, p = .049) and 35 min (HRW: 0.44 ± 0.30, placebo: 0.28 ± 0.28, p = .029) of rest sitting. Ln SDNN was significantly increased after HRW administration when compared to placebo in 45 min (HRW: 4.41 ± 0.42 ms, placebo: 4.28 ± 0.31 ms, p = .049) of rest sitting. Conclusions: Acute HRW ingestion induced a relative increase in sympathetic activity between 25 and 35 min post-ingestion, whereas vagal activity was not affected.
Keywords: Female; Sympathetic Nervous System; vodík; autonomní nervový systém; Autonomic Nervous System; mladý dospělý; ženské pohlaví; Adolescent; lidé; klinická studie jako téma; Clinical Studies as Topic; vodíková voda; voda; Water; Hydrogen; sympatický nervový systém; Young Adult; mladiství; Humans